2013
DOI: 10.4103/2249-4863.120728
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and anti-microbial sensitivity of organisms causing community acquired pneumonia: A single hospital study

Abstract: Objective:The objective of this study was to identify the common etiological pathogens causing community acquired pneumonia (CAP) in our hospital and sensitivity patterns to the common antibiotics used.Materials and Methods:This study was undertaken in a 750 bedded multi-specialty referral hospital in Kerala catering to both urban and semi-urban populations. It is a prospective study of patients who attended the medical out-patient department and those admitted with a clinical diagnosis of CAP, during the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
3
17
0
1
Order By: Relevance
“…In most of the previous studies predominant number of patients were older (>50 yrs). [8,11] Most of our patients presented with cough (95%) and fever which are same as found in previous studies.…”
Section: Discussion:-supporting
confidence: 78%
See 1 more Smart Citation
“…In most of the previous studies predominant number of patients were older (>50 yrs). [8,11] Most of our patients presented with cough (95%) and fever which are same as found in previous studies.…”
Section: Discussion:-supporting
confidence: 78%
“…[6,8,9] In our study we found occurrence of klebsiella around 9% and comes 3 rd after Pseudomonas(11%). One study from Srinagar found Psudomonas as commonest cause of CAP.…”
Section: Discussion:-mentioning
confidence: 72%
“…Majority of the bacteria were sensitive to imipenem and amikacin which is similar to other studies. 22 No case of colistin resistance in Acinetobacter and vancomycin resistance in Staphylococcus aureus were observed in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Study conducted by Shalini et al (2011) 13 revealed that Klebsiella (20.3%), Pseudomonas (9.1%) and S. aureus (6.3%) were the most common organisms isolated. Menon RU et al (2013) 14 conducted a similar study and found that S. pneumonia was the most common etiological agent followed by K. pneumoniae, Pseudomonas aeruginosa. Sputum (236), Throat swab (91), Tracheal (30) were the major samples collected from patients infected with RTI during the study period.…”
Section: Discussionmentioning
confidence: 90%